A nested model of the Nordic Seas - Sandø, Anne Britt; Drange, Helge (Zenodo, 2007)
A nested version of the Miami Isopycnic Coordinate Ocean Model (MICOM) has been st up on the Nordic Seas in order to give a quantitative description of the changes of the main currents there. the nested model is initialized with interpolated model data from a global version of MICOM. It is forced by NCEP-NCAR synoptic fields over the integration period 1948-2003, including realistic river runoff. The model has been validated against observations in the Iceland-Faroe-Scotland ridge region, and reproduces circulation, temperature and salinity quite well. NERSC Technical Report no. 268